Particulate Matter Exposure During Oocyte Maturation: Cell Cycle Arrest, ROS Generation, and Early Apoptosis in Mice - Jo, Yu-Jin; Yoon, Seung-Bin; Park, Byoung-Jin; Lee, Sang Il; Kim, Ki Jin; Kim, Se-Yong; Kim, Minseong; Lee, Jun-Ki; Lee, Sang-Yong; Lee, Dong-Ho; Kwon, Taeho; Son, Yeonghoon; et al. (Frontiers in Cell and Developmental Biology, 2020)
Particulate matter (PM) is a general atmospheric pollutant released into the air by an anthropogenic and naturally derived mixture of substances. Current studies indicate that fine dust can result in different health defects, including endothelial dysfunction, asthma, lung cancer, cardiovascular diseases, uterine leiomyoma, deterioration in sperm quality, and overall birth impairment. However, the most prominent effects of PM10 (diameter < 10 µM) exposure on the female reproductive system, especially with respect to oocyte maturation, remain unclear. In the present study, maturing mouse oocytes were treated with PM10 and the phenotypes of the resulting toxic effects were investigated. Exposure to PM10 led to impairment of maturation capacity by inducing cell cycle arrest and blocking normal polar body extrusion during in vitro maturation and activation of fertilization of mouse oocytes. Additionally, defects in tubulin formation and DNA alignment were observed in PM10-treated oocytes during metaphase I to anaphase/telophase I transition. Moreover, PM10 induced reactive oxygen species generation, mitochondrial dysfunction, DNA damage, and early apoptosis. Taken together, these results indicate that PM10 exposure leads to a decline in oocyte quality and affects the subsequent embryonic development potential of mammalian oocytes.